Opening Avenues in Nagaland…. Intercropping turmeric and ihum paddy in pineapple brings cheers - Sharma, Anamika; Rabi, Kolom; Deka, Bidyut C (Indian Horticulture, 2019)
Introduction: Pineapple, an important fruit in Dimapur district in Nagaland, comes to flowering only after 15-18 month of plantation. Farmers cultivate pineapple as a sole crop and spend a large sum of money and labour of weeding, leading to an increase cost of cultivation without any income during first year of its plantation. So, effort were made to generate some amount of income during the pre-bearing stage of pineapple by growing turmeric and Jhum paddy, utilizing the space available between two rows of pineapple. These practices not only suppress weed growth in inter-row spaces, but also reduce the cost of wedding during the first year of planting.